Spectrofluorimetric determination of serotonin and 5-hydroxyindoleacetic acid in urine with different cyclodextrin media - Bracamonte, Angel Guillermo (2011)
Alternative and sensitive spectrofluorimetric methods for the determination of hydroxyindoles, such as serotonin (5HT) and 5-hydroxyindoleacetic acid (5HIA), were developed on the basis of supramolecular interaction with cyclodextrin (CD) nanocavities (βCD and hydroxypropyl-βCD, HPCD) at different pH values. Both substrates and receptors have acidic protons, therefore the interactions produced in different systems were considered. The effects of neutral CD at pH 2.00 and 6.994, and of anionic CD at pH 13.00 on the specific acid-base species of the compounds at each pH were determined. In all the conditions studied, the fluorescence of the substrates in the presence of CD increased. The association constants (KA, mol-1 L) between the substrates and CD were determined (30-300) and interpreted. A zero-crossing first-derivative spectrofluorimetric method with and without HPCD was developed for the simultaneous determination of 5HT and 5HIA. The limits of detection (LD, ng mL-1) for the best conditions were 0.37 for 5HT and 0.50 for 5HIA at pH 2.00 with HPCD. These LD proved to be better than others reported. The applicability of the direct and derivative spectrofluorimetric methods to urine samples was demonstrated with good recoveries 92-110% and R.S.D. 1-10%. © 2010 Elsevier B.V.All rights reserved.